Nordic Families, Children and Early Childhood Education - Garvis, Susanne; Harju-Luukkainen, Heidi; Sheridan, Sonja; Williams, Pia (Studies in Childhood and Youth, 2019)
Largely as a result of social policies and cultural factors, the Nordic countries continually score high in lifestyle measures, quality of life and children's outcomes. This book brings together authors from the Nordic countries (Denmark, Finland, Iceland, Norway and Sweden) to share knowledge and understanding regarding families, children, primary education and children's leisure time activities. The empirical research and theoretical contributions provide important insights into the 'Nordic model' and explore the issues facing Nordic countries. The book reveals that while there are many similarities across the countries, differences also arise. The content of the book is more relevant now than ever, as countries look at better ways to support their populations. Nordic Families, Children and Early Childhood Education will be of interest to students and scholars across a range of disciplines, including Education, Sociology and Social Policy.